Five-Year Prospective Follow-Up of Patients with Hepatitis C Virus Infection Treated with Direct-Acting Antiviral Agents - Zhang Y; Xia H; Fan L; Jiang L; Yang B; Wang F (Infection and Drug Resistance)
Yaping Zhang,1,2,* Huan Xia,3,* Luchang Fan,1 Lu Jiang,4 Bin Yang,2 Fengmei Wang4,5 1The Third Central Clinical College of Tianjin Medical University, Tianjin Medical University, Tianjin, 300170, People’s Republic of China; 2Tianjin Key Laboratory of Extracorporeal Life Support for Critical Diseases, Institute of Hepatobiliary Disease, Nankai University Affiliated Third Central Hospital, Tianjin, 300072, People’s Republic of China; 3Department of Infectious Diseases, Tianjin Second People’s Hospital, Tianjin, 300192, People’s Republic of China; 4Department of Hepatology and Gastroenterology, Tianjin First Central Hospital, Tianjin, 300192, People’s Republic of China; 5Tianjin Key Laboratory of Molecular Diagnosis and Treatment of Liver Cancer, Tianjin First Central Hospitial, Tianjin, 300192, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fengmei Wang; Bin Yang, Email wangfengmeitj@126.com; bioyang@126.comPurpose: The research intended to present prospective data on the long-term prognosis of individuals with hepatitis C virus (HCV) infection who received direct-acting antiviral agent (DAA) treatment.Patients and Methods: Patients who received DAA treatment at Tianjin Third Central Hospital and Tianjin Second People’s Hospital were prospectively enrolled and subsequently underwent a longitudinal follow-up. This research monitored occurrences of virological relapse, hepatocellular carcinoma (HCC), mortality, and liver disease progression. The annualized incidence rates (AIRs), cumulative incidence rates of adverse events and risk factors were investigated. Changes in liver stiffness measurement (LSM), aspartate aminotransferase-to-platelet ratio index (APRI) score, fibrosis-4 (FIB-4) index, as well as the albumin-bilirubin (ALBI) scores were also documented.Results: A total of 862 individuals were followed up for 4.86 (P25, P75; 4.48, 5.48) years. The proportion of all participants with undetectable HCV-RNA exceeded 98% at all follow-up time points. Patients experienced virological relapse, HCC, death and disease progression with a cumulative AIRs of 1.03% (95% confidence interval [CI] 0.6– 1.5), 1.76% (95% CI 1.2– 2.3), 1.51% (95% CI 1.0– 2.0), and 5.81% (95% CI 4.8– 6.8), respectively. Cirrhotic patients were at a heightened risk of virological relapse (adjusted hazard ratio [aHR] 3.20, 95% CI 1.59– 9.75; p = 0.016), HCC (aHR 6.57, 95% CI 2.66– 16.28; p < 0.0001), and unfavorable prognosis (aHR 6.93, 95% CI 2.56– 18.74; p < 0.0001). Additionally, patients with diabetes faced an elevated risk of HCC (aHR 2.33, 95% CI 1.05– 5.15; p = 0.038) and poor prognosis (aHR 2.72, 95% CI 1.13– 6.55; p = 0.026). Furthermore, liver stiffness measurement (LSM) exhibited a significant decrease compared to baseline. Additionally, patients in the cirrhosis group showed reductions in APRI score, FIB-4 index and ALBI score to different degrees.Conclusion: Cirrhotic patients exhibited increased susceptibility to virological relapse, HCC, unfavorable prognosis, and liver disease progression following DAA treatment. Consequently, it is imperative to implement a rigorous monitoring protocol for all cirrhotic patients after DAA treatment.Keywords: chronic hepatitis C, cirrhosis, direct-acting antiviral agents, sustained virologic response, follow-up